ANALISIS TERHADAP FAKTOR BERPENGARUH PADA PENINGKATAN KINERJA KARYAWAN (STUDI PADA UBUD RAYA RESORT) - Ni Made Dwi Anggariani; I Gusti Ayu Wimba; I Gede Aryana Mahayasa (Fakultas Ekonomi Universitas Warmadewa, 2024)
The purpose of this study is to determine the effect of the influence of self-efficacy, work discipline and work environment on employee performance at Ubud Raya Resort. This study, which became the study population was all employees at Ubud Raya Resort as many as 34 people. The sampling method used is the saturated sampling method, which is a sample collection technique when all members of the population are used as samples. The test techniques used are research instrument tests, classical assumption tests, multiple linear regression analysis, t tests and F tests. The results obtained in this study are: Self efficacy has a positive and significant effect on employee performance. Work Discipline has a positive and significant effect on employee performance. The physical work environment has a positive and significant effect on employee performance. Self-efficacy, work discipline, and physical work environment simultaneously have a significant effect on employee performance at Ubud Raya Resort. Suggestions that can be given are Ubud Raya Resort employees can increase confidence in work, increase enthusiasm at work to be able to motivate themselves, obey applicable regulations, be responsible and have self-awareness of duties and obligations at work in order to work with maximum results.